2017
DOI: 10.5505/tjtes.2017.83103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of selfie-related injuries and deaths

Abstract: Selfie-related injuries and deaths have increased in the past years. Particularly, teenagers and young adults are at high risk for selfie-related traumas and deaths; therefore, drastic measures should be taken to reduce their incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…However, the association might not be strong because social media use and selfie-taking are actually different behaviors. Similarly, some degrees of association were found between the SBS and psychological distress because some individuals' selfitis behavior may impair their psychological health (Dokur et al 2018;Pantic et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association might not be strong because social media use and selfie-taking are actually different behaviors. Similarly, some degrees of association were found between the SBS and psychological distress because some individuals' selfitis behavior may impair their psychological health (Dokur et al 2018;Pantic et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We have also come across cases of fatality of individuals trying to take dangerous sel ies. The irst (Domlur et al, 2018). Since then, there have been 259 deaths reported all over the world (Singh, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable discussion on the basis for this behavior, with suggestions that excessive selfie-taking and sharing on social media sites are associated with narcissism and psychopathology [4] representing the "act of an egotistical individual keen on self-promotion" [5]. Alternatively, other authors have more charitably, although possibly less plausibly, suggested that it may instead be a "complex and rich means of communicating one's inner state" [6].…”
mentioning
confidence: 99%
“…The number of cases has been doubling each year, with the mean age of victims being 23.3 years. The majority are male (82%) students and/or tourists [1,4]. A study looking over the time range October 2011 to November 2017 identified 259 fatalities [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation